Endogenous neurotrophin-3 promotes neuronal sprouting from dorsal root ganglia - Xu-yang Wang (Neural Regeneration Research, 2015)
In the present study, we investigated the role of endogenous neurotrophin-3 in nerve terminal sprouting 2 months after spinal cord dorsal root rhizotomy. The left L 1-5 and L 7 -S 2 dorsal root ganglia in adult cats were exposed and removed, preserving the L 6 dorsal root ganglia. Neurotrophin-3 was mainly expressed in large neurons in the dorsal root ganglia and in some neurons in spinal lamina II. Two months after rhizotomy, the number of neurotrophin-3-positive neurons in the spared dorsal root ganglia and the density of neurite sprouts emerging from these ganglia were increased. Intraperitoneal injection of an antibody against neurotrophin-3 decreased the density of neurite sprouts. These findings suggest that endogenous neurotrophin-3 is involved in spinal cord plasticity and regeneration, and that it promotes axonal sprouting from the dorsal root ganglia after spinal cord dorsal root rhizotomy.